A modified decoupling scheme for receiving antenna arrays with application to DOA estimation. Issue 2 (21st August 2012) - Parhizgar, Naser; Alighanbari, Abbas; Masnadi‐Shirazi, Mohammad‐Ali; Sheikhi, Abbas
Abstract Mutual coupling in antenna arrays can critically degrade the performance of subsystems, such as those aiming at the estimation of the direction of arrival (DOA) of incident signals. In this article, an accurate form of mutual impedance matrix (MIM) and decoupling methodology is introduced. The methodology for computing the MIM is presented. In the modified MIM and decoupling method, extreme care has been taken to account for all self‐impedance and mutual impedance terms, relating to the mutual coupling effects. It is shown that the new method results in an essential improvement in DOA estimation applications. The resolution and accuracy, achieved using the modified MIM and decoupling methodology, are unmatched with those of the previous techniques. © 2012 Wiley Periodicals, Inc. Int J RF and Microwave CAE, 2013.